Authentic Practice of Writing Arabic Language Teaching Materials Oriented to Higher-Order Thinking Skills (HOTS): A Study of Arabic Language Education Student Projects - Toni Gunawan Rambe; Sabarudin Sabarudin; Mahmudah Mahmudah (Al-Kalimat: Journal of Linguistic and Arabic Teaching, 2026)
This study investigates the implementation of authentic practice in the writing of Arabic teaching materials oriented toward Higher-Order Thinking Skills (HOTS), focusing on a project conducted by students of Arabic Language Education at UIN Sunan Kalijaga Yogyakarta. The development of effective teaching materials is crucial for supporting meaningful language learning, especially for a globally important language like Arabic. While over 450 million native speakers use Arabic and it serves as an official language of international institutions , existing research emphasizes the need for contextualized and engaging materials to enhance learner motivation and comprehension (Al‑Harbi, 2020). Using a descriptive qualitative approach, data was collected through participatory observation, semi-structured interviews, and document analysis of student-produced teaching resources. Analysis was conducted thematically, incorporating triangulation and member checking to ensure validity. Results indicate that students apply authentic practices by integrating real-life themes—such as Arab culture, technology, and social issues—into materials; co-developing multimedia modules; and engaging learners through surveys and interactive activities. These methods have a positive impact on students' HOTS, with 78% reporting improved critical thinking and 90% reporting enhanced creativity. However, challenges persist: students face limited access to current Arabic references, technological constraints, and a lack of instructional guidance for HOTS-based material design. Addressing these challenges requires institutional support in the form of digital resource access, HOTS competency workshops, and enhanced pedagogical supervision. Future research is encouraged to undertake longitudinal studies tracking HOTS development and experimental designs to evaluate pedagogical outcomes more rigorously.